Numerical Study of Soft Soil Improvement Using Prefabricated Vertical Drain in Paser Airport East Kalimantan, Indonesia - Aditia Febriansya; Dewi Amalia; Mulyadi Yuswandono; Antonius Siswanto; Sinta Nuraeni; Talitha Rahma Avinka (Potensi: Jurnal Sipil Politeknik, 2022)
In this article, the effect of using Prefabricated Vertical Drain as a soil improvement on the time it takes for consolidation to settle in the construction of runway embankments at Paser Airport, East Kalimantan, Indonesia using numerical methods will be discussed. Based on the Indonesian Soft Soils Distribution Map and the results of the Standard Penetration Test conducted the runway area is dominated by soft clay to a depth of 24 meters. The characteristics of soft soils have low shear strength, high compressibility and low permeability which can cause large settlements over a long period of time. In numerical analysis, Prefabricated Vertical Drain is combined with preloading to speed up consolidation time. Based on the analysis results, the minimum pore pressure condition before soil improvement is reached within 36.36 years, whereas after soil improvement, the time for settlement is significantly reduced to 0.17 years or 63.22 days. The preloading height is calculated so that the final embankment elevation is reached when the settlement has been completed. Manual analysis was performed to obtain a comparison of the duration of settlement using numerical methods.